Radio Link Planning Made Easy with a Telegram Bot - Zennaro, Marco; Rainone, Marco; Pietrosemoli, Ermanno (Smart Objects and Technologies for Social Good, 2017)
Traditional radio planning tools present a steep learning curve. We present BotRf, a Telegram Bot that facilitates the process by guiding non-experts in assessing the feasibility of radio links. Built on open source tools, BotRf can run on any smartphone or PC using Telegram. Running it on a smartphone has the added value that the Bot can leverage the internal GPS to capture the current coordinates. BotRf can be used in low bandwidth environments as the generated data traffic is very limited. We present an example of its use in Venezuela.